Technical limitations of dual-energy CT in neuroradiology: 30-month institutional experience and review of literature - Dinkel, Julien (Journal of neuroInterventional surgery, 2015)
Background Dual-energy CT (DECT) has been shown to be a useful modality in neuroradiology. Objective To assess failure modes and limitations of DECT in different neuroimaging applications. Patients and methods Dual-source DECT scans were performed in 72 patients over 30 months to differentiate contrast agent staining or extravasation from intracranial hemorrhage (ICH) (n=40); to differentiate calcium from ICH (n=2); for metal-artifact reduction (n=5); and for angiographic assessment (n=25). A three-material decomposition algorithm was used to obtain virtual non-contrast (VNC) and iodine (or calcium) overlay images. Images were analyzed in consensus by two board-certified radiologists to determine the success of the algorithm and to assess confounding factors. Furthermore, a dilution experiment using cylinders containing defined heparinized swine blood, normal saline, and selected iodine concentrations was conducted to assess other possible confounding factors. Results Dual-energy analysis was successful in 65 (90.2%) patients. However, the algorithm failed when images were affected by beam hardening (n=3, 4.2%), the presence of a fourth material (parenchymal calcification) (n=3, 4.2%), or motion (n=1, 1.4%). In the dilution experiment, a saturation effect was seen at high iodine concentrations (≥37 mg/ml). VNC and iodine overlay images were not reliable above this concentration, and beam-hardening artifacts were noted. Conclusions DECT material decomposition is usually successful in neuroradiology. However, it can only distinguish up to three preselected materials. A fourth material such as parenchymal calcium may confound the analysis. Artifacts such as beam hardening, metallic streak, or saturation effect can also impair material decomposition.
Gesehen am 21.02.2017